The study of reactions influencing the biomass steam gasification process - Franco, C.; Pinto, F.; Gulyurtlu, I.; Cabrita, I. (FUEL, 2003)
Steam gasification studies were carried out in an atmospheric fluidised bed. The gasifier was operated over a temperature range of 700900 degreesC whilst varying a steam/biomass ratio from 0.4 to 0.85 w/w. Three types of forestry biomass were studied: Pinus pinaster (softwood), Eucalyptus globulus and holm-oak (hardwood). The energy conversion, gas composition, higher heating value and gas yields were determined and correlated with temperature, steam/biomass ratio, and species of biomass used. The results obtained seemed to suggest that the operating conditions were optimised for a gasification temperature around 830 degreesC and a steam/biomass ratio of 0.6-0.7 w/w, because a gas richer in hydrogen and poorer in hydrocarbons and tars was produced. These conditions also favoured greater energy and carbon conversions, as well the gas yield. The main objective of the present work was to determine what reactions were dominant within the operation limits of experimental parameters studied and what was the effect of biomass type on the gasification process. As biomass wastes usually have a problem of availability because of seasonal variations, this work analysed the possibility of replacing one biomass species by another, without altering the gas quality obtained. (C) 2002 Elsevier Science Ltd. All rights reserved.
The following values have no corresponding Zotero field: pub-location: THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, OXON, ENGLAND publisher: ELSEVIER SCI LTD
Keywords: biomass; fluidised bed; gasification; steam